Peran Amil Zakat dalam Meningkatkan Kesadaran Zakat Profesi Pada Laznas Al-Azhar Jakarta Selatan - Wisnu Nugraha; Muhammad Zen (Al Maal: Journal of Islamic Economics and Banking, 2020)
The purpose of this research is for knowing the jobs and the position of zakat agency, the function of zakat agency in increasing awareness of profession zakat, contributing factors and presecutor factors. This research used qualitative method by analysing of descriptive data. The researcher gave a description of discovery which was found by Laznas Al-Azhar. This research used data collection by observation in the location, interviewing and be completed by data documentation. The result of the function of zakat agency in increasing awareness of profession zakat is all zakat agencies have been doing their jobs professionally and zakat agency of Laznas Al-Azhar has the important contribution in increasing awareness of profession zakat. The position of zakat agency is the best and the main function of zakat agency is same generally, it is giving education. While from their jobs are accumulation, writing down, managing and distribution for mustahik as eight asnaf which is from Al-Quran.